Populasi dan Kesesuaian Habitat Langkap (Arenga obtusifolia Mart.) di Cagar Alam Leuweung Sancang, Jawa Barat - Usmadi, Didi; Hikmat, Agus; Witono, Joko Ridho; Prasetyo, Lilik Budi (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTThe growth and regeneration of langkap in natural habitat is very fast and has invasive tendencies. The aim of study was to analyze the population and population structure of langkap in Leuweung Sancang Nature Reserve, and build spatial models of habitat suitability langkap in Leuweung Sancang Nature Reserve. Data were collected using a sampling method with a number of plots along the transect line. Langkap has become the dominant species in Leuweung Sancang Nature Reserve on saplings and pole with population structure shows an normally structure population. Analysis of spatial modelling on habitat suitability of langkap through binary logistic regression with independent variables in the form of the Forest Canopy Density (FCD), slope, distance from the river and Normalized Difference Moisture Index (NDMI) has been able to predict habitat suitability of langkap in Leuweung Sancang Nature Reserve, i.e. 61,10% of the Leuweung Sancang Nature Reserve suitable as habitat langkap and 38,90% of the Leuweung Sancang Nature Reserve is not suitable as habitat langkap.Â Keywords: Langkap, Arenga obtusifolia, habitat suitability, spatial modeling, Leuweung Sancang Nature Reserve.Â